Biophysical and spectroscopical insights into structural modulation of species in the aggregation pathway of superoxide dismutase 1 - Vijay Raj Tomar; Shilpa Sharma; Soumik Siddhanta; Shashank Deep (Communications Chemistry)
Abstract Superoxide dismutase 1 (SOD1) aggregation is implicated in the development of Amyotrophic Lateral Sclerosis (ALS). Despite knowledge of the role of SOD1 aggregation, the mechanistic understanding remains elusive. Our investigation aimed to unravel the complex steps involved in SOD1 aggregation associated with ALS. Therefore, we probed the aggregation using ThT fluorescence, size-exclusion chromatography, and surface-enhanced Raman spectroscopy (SERS). The removal of metal ions and disulfide bonds resulted in the dimers rapidly first converting to an extended monomers then coming together slowly to form non-native dimers. The rapid onset of oligomerization happens above critical non-native dimer concentration. Structural features of oligomer was obtained through SERS. The kinetic data supported a fragmentation-dominant mechanism for the fibril formation. Quercetin acts as inhibitor by delaying the formation of non-native dimer and soluble oligomers by decreasing the elongation rate. Thus, results provide significant insights into the critical steps in oligomer formation and their structure.